Private Equity and Employees - Martin Olsson; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2012)
Using linked employer-employee data from Sweden, a difference-in-difference approach, and 201 private equity buyouts undertaken between 1998 and 2004, we show that unemployment risk declines and labor income increases for employees in the wake of a private equity buyout. Unemployment risk declines despite lower employment growth for continuing establishments attributable to hiring freezes rather than to layoffs and a lack of change in firm level employment growth. A plausible explanation is relaxed financial constraints: the effects are strongest in industries dependent on external finance for growth, for non-divisional buyouts, and for buyouts just prior to 2001.
Keywords: G24; G32; G34; J20; L25; 330; Buyouts; Employment; Financial Constraints; LBO; Private Equity; Restructuring; Risikokapital; Übernahme; Beschäftigung; Organisatorischer Wandel; Schweden